Cyberculture and digital hygiene in the educational process - Bohdan Kravets; Yaroslav Galitskiy; Nataliia Denysenko (II. Rákóczi Ferenc Kárpátaljai Magyar Egyetem, 2025)
Abstract. In the 21st century, the educational process is inseparable from digital technologies. The rapid growth of online communication, e-learning platforms, and artificial intelligence tools has created a cultural phenomenon known as cyberculture [1, ch. 1; 2, sec. 2]. It transforms the way knowledge is delivered, shapes digital identities, and affects social interactions. This paper explores the role of cyberculture in education, digital hygiene as a component of security, challenges and risks of digitalization, ethical issues, and future perspectives [3, sec. 3; 5, sec. 2]. 1. Introduction. Cyberculture is becoming a key component of education. It is not limited to technical tools but includes new forms of communication, online communities, and cultural practices [1, ch. 1]. At the same time, digitalization requires responsible and safe interaction with digital environments [2, sec. 3]. 2. The Role of Cyberculture in Education 2.1. Active participation. Students move from passive knowledge consumers to active creators through discussions, collaboration, and digital projects [2, sec. 2]. 2.2. Digital identity and communities. Online spaces shape student identity and values, requiring responsibility and awareness [1, ch. 2; 5, sec. 3]. 3. Digital Hygiene as a Security Component 3.1. Data protection. Digital hygiene includes practices of strong passwords, phishing awareness, and digital footprint control [3, sec. 2]. 3.2. Well-being. Screen time management is critical for psychological balance and productivity [9, sec. 1].
Teljes kiadvány: https://kme.org.ua/uk/publications/rol-bezpeki-v-transkordonnomu-ta-mizhnarodnomu-spivrobitnictvi/
Keywords: cyberculture; misinformation; education